DNA methylation and immune evasion in triple-negative breast cancer: challenges and therapeutic opportunities - Cai, Wen-yu; Cai, Xin-xian; Fei, Yi-ran; Ye, Rui; Song, Ding-ming; Hu, Dan; Zhang, Wan-wan; Xia, Ming-fei; Yang, Xiao-xiao (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer characterized by the lack of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Chemotherapy remains the primary treatment option, yet TNBC frequently develops resistance, leading to relapse and metastasis. Emerging evidence highlights the potential of combining DNA methylation inhibitors with immune checkpoint inhibitors (ICIs). DNA methylation contributes to immune escape by silencing immune-regulatory genes, thereby reducing the tumor’s visibility to immune cells. Reversing this epigenetic modification can reinvigorate immune surveillance and enhance the efficacy of immunotherapies. This review discusses the role of DNA methylation in TNBC progression and immune evasion, focusing on recent advances in combination therapies involving DNA methylation inhibitors and ICIs. We discuss the underlying mechanisms that enable these therapeutic synergies, preclinical and clinical evidence supporting the approach, and the challenges posed by tumor heterogeneity, drug resistance, and toxicity. Finally, we explore the potential for personalized treatment strategies incorporating multi-omics data to optimize therapeutic outcomes. The integration of epigenetic therapies and immunotherapy offers a promising avenue for improving survival in TNBC patients.